(untitled) (Community Based Medical Journal, 2013)
The value of a single Widal test was evaluated on 100 clinically suspected typhoid fever cases and 40 age-sex matched controls, in the Department of Microbiology, Mymensingh Medical College during the period from July 2006 to June 2007. Blood culture and Widal test with rising titre were performed in all patients. Among 100 clinically suspected of typhoid fever cases, 35 were subsequently confirmed on the basis of positive blood culture for S. typhi and/or significant rising titre of Widal test. The sensitivity, specificity, positive and negative predictive value of a single Widal test was found as 42.85%, 85.00%, 71.42% and 62.96% respectively. Thus, an elevated levels of agglutinating O and H antibodies as measured in a single Widal test might be helpful in making a presumptive diagnosis of typhoid fever if interpreted with care. DOI: http://dx.doi.org/10.3329/cbmj.v2i1.14180 Community Based Medical Journal Vol.2(1) 2013 34-38